Enhancing Magnetic Cooperativity in Fe(II) Triazole‐based Spin‐crossover Nanoparticles by Pluronic Matrix Confinement. Issue 17 (23rd July 2020) - Zoppellaro, Giorgio; Čépe, Klára; Aparicio, Claudia; Ugolotti, Juri; Zbořil, Radek
Abstract: Polymeric one‐dimensional (1D) triazole‐based Fe II spin crossover nanoparticles have been entrapped in pluronic P123 matrix, forming nanorods in which the interaction between host (P123) and guest (Fe II complex) promoted high reproducibility of the spin crossover process, significant shifts of the transition temperatures ( T ↑=370 K, T ↓=338 K for the P123 entrapped material vs the literature values of T ↑=358 K, T ↓=341 K for the neat/polymer free system) and larger magnetic hysteresis width. Abstract : One‐dimensional (1D) triazole‐based Fe II spin crossover nanoparticles have been entrapped in organic P123 matrix, imparting greater reproducibility of the spin crossover process, as witnessed in the stability of the magnetic hysteresis width ( ΔT =32 K) following sequential heating and cooling cycles, and significant shifts of the spin transition temperatures compared to the polymer free complex.